CONVERSATIONAL ANALYSIS OF TURN-TAKING IN ENGLISH TEACHING ACTIVITIES ON THE JUNIOR HIGH SCHOOL LEARNING MODEL VIDEO - Winda, Ayang; Nurfithri; Muhammad Fikri Taufik (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
Basically, the teacher will always start a conversation and even give turns with students in class to carry out the right learning process. Conversation consists of two or more participants taking turns and only one participant speaking at any time. To analyze conversation interaction between two people or more the appropriate theory was known as Conversation Analysis, one of the strategies is Turn-taking. For authentic conversations, turn-taking is a basic component. It refers to the phenomenon of changing the roles of the speaker and the listener when they are engaged in conversations. This happens with remarkably little overlapping speech and remarkably few silences. Based on the data on this study that used a qualitative case study method, the dominant mechanism of turn-taking between teachers and students during English learning activities is yielding the floor, it is about 57.1%. From this study, the researchers also can find out that turn-taking has some impacts on students one of them is to be more active and think critically in learning activities.